STATISTICAL OPTIMIZATION OF CHITIN BIOCONVERSION TO PRODUCE AN EFFECTIVE CHITOSAN IN SOLID STATE FERMENTATION BY Asperigellus flavus - & et al., Yonis (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this study is to develop a bioconversion process of chitin to chitosan in solid-state fermentation. A classical optimization of one factor at the time was performed and revealed that maximum chitin deacetylase (CDA) production can be obtained in corn medium moisturized with mineral salt solution and with an initial moisture of 1:1 level (w/v). Results showed that 3% of spore inoculum contained 1× 106 provided maximum production of CDA enzyme (219.5 U/g solid medium) after 5 days of incubation. Moreover, process parameters were systemically evaluated to improve the bioconversion of chitin to chitosan by statistical optimization using response surface methodology. The maximum production of chitosan of was reached to 27.3 mg/g media by using 1% chitin after 15 days of incubation with predicted chitosan concentration of 26.2mg/g. From ANOVA table. Time was the most significant factor in chitosan production with F-value 1014.5 and construction of empirical model building with determination coefficient R2=0.994. The physiochemical characteristic of the produced chitosan in terms of degree of deacetylation, viscosity, chemical structure revealed high compatibility with the commercial chitosan. Result revealed that the chitosan produced in this study has a broad spectrum of antimicrobial activity against human pathogens: including Streptococcus spp., Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Candida albicans.